Hate Speech Addressed to President Joko Widodo in Online Media: Impoliteness Strategies Analysis - Yuri Widiantho (LingPoet: Journal of Linguistics and Literary Research, 2020)
This study aims to examine hate speeches that addressed to President Joko Widodo. This study used a qualitative descriptive approach that establishes the requirement that a study must be carried out on the basis of existing facts. The sources of data of this study were obtained from several mass media and social media from the haters of President Joko Widodo. This research data is in the form of phrase and clause which contained in status, caption, and video. The collected data was analyzed using data condensation, data display and data verification techniques to find out the types of hate speeches. The results showed that Frighten 42.9 %, and Call the other names 28.5 %, were the dominant types of hate speeches that had been viral and processed by the police used compared with the other types. Since the data are the products of violations of law, therefore it was proved that most speeches produced were categorized against the Law No 19 of 2016 about Information and Electronic Transactions.